Dielectric characteristics of GaSe nanocrystals intercalated with hydrogen - Kaminskii, V.I.; Kovalyuk, Z.D.; Netyaga, V.V.; Boledzyuk, V.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The results of investigations of dielectric characteristics of GaSe nanocrystals
and their hydrogen intercalates are presented. By using the impedance spectroscopy
method, it is established that the dielectric spectra of GaSe and HxGaSe (х = 0.07 and
0.14) nanocrystals correspond to the exponent law of dielectric response. It is found that
there is an increase of the dielectric constant ε∞ for the intercalated samples in
comparison with that of the initial sample. We have obtained the frequency dependences
of the real and imaginary parts of the conductivity, whose dispersion is due to the
presence of two-dimensional defects. Equivalent electrical circuits which determine
electrical characteristics of the crystals under study are proposed.